Pengaruh Faktor Makroekonomi Terhadap Nilai Aktiva Bersih pada Reksa Dana Saham Syariah - Indah Sulsitiyowati; Destian Arshad Darulmalshah Tamara; Benny Barnas (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Equity Sharia Mutual Funds are mutual funds whose portfolio contains 80% of sharia equity securities. In 2019, there was a significant decrease in the NAV, while the number of mutual fund investors increased. This study aims to determine the effect of macroeconomics factors such as the BI Rate, ISSI, and Exchange Rate on the NAV of Equity Sharia Mutual Funds in Indonesia. Sample selection using purposive sampling method an multiple linear regression analysis. The expected output form is an equation model that can show the influence of the BI Rate, ISSI, and Exchange Rate on NAV simultaneously or partially. The results of this study are BI Rate, ISSI, and the Exchange Rate have a simultaneous effect on NAV. Partially the BI Rate and Exchange Rate have a significant effect on NAV while ISSI has no significant effect on NAV.